Knowledge Management practices: Teachers perception - Babar, Muhammad Ayoob Khan; Jummani, N. B.; Mahmood, Sheikh Tariq; Amin, Sufi; Uddin, Hafeez (European Scientific Journal, ESJ, 2016)
In today’s world, Knowledge Management is considered as a key to organizational growth and competitiveness. This study aim was to investigate the perception of teachers about main factors affecting the teaching learning process in adopting and applying Knowledge Management. The main objectives of the study were (i) to explore the existing Knowledge Management Practices of teachers in International Islamic University Islamabad (ii) to find out the difficulties regarding knowledge management and (iii) to examine the factors affecting the application of Knowledge Management Practices in improving the performance of teachers. Qualitative method was used as mode of inquiry. Data was collected through an Interview guide. Concurrent exploratory design was used in the study while collecting and analyzing data. Qualitative data was analyzed through content analysis and percentage.